The Social Banditry in the Rural Areas of Rembang by the End of the 19th Century and at the Beginning of the 20th Century - Warto, Warto (ASPENSI in Bandung, Indonesia, 2011)
ABSTRACT: The social banditry is the act of crime committed by the residents of a village or the people in the low economic and social stratum in order to fulfill their basic needs. Such an act is done due to the structural pressure which depresses the people in accessing the natural resources that support their lives. This structural pressure kept increasing in the rural areas of Rembang by the end of the 19th century, particularly after the issuance of the law on forestry in 1865 that enabled the forestry capitalism to be established. The limitation in the peopleâs access to the state forest as the manifestation of the domain concept and the exploitation of the teak forests done by the private businessmen became the trigger to the increasing acts of crime in the rural areas of Rembang. The scarcity of the local economic resources due to such natural factors as barren land and structural factors as the result of the penetration of the external power became the main trigger to the social banditry to take place in Rembang. There were many kinds of social banditry, such as illegal logging, robbery, âkecuâ (burglary), theft of possessions, etc. which were done against the assets owned by both the state and the individuals/groups.KEY WORDS: Social banditry, forest village, Rembang area, economic resources, and colonial exploitation.About the Author: Dr. Warto is a Lecturer at the Faculty of Letter and Fine Art UNS (State University of Surakarta), Jalan Ir. Sutami 36-A Surakarta 57126, Central Java, Indonesia. He can be reached at: warto_file@yahoo.com Â How to cite this article? Warto. (2011). âThe Social Banditry in the Rural Areas of Rembang by the End of the 19th Century and at the Beginning of the 20th Centuryâ in TAWARIKH: International Journal for Historical Studies, Vol.3(1) October, pp.47-64. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (August 7, 2011); Revised (September 9, 2011); and Published (October 28, 2011).